Analysis of Class Teachers in Addressing Physical Education Learning in Primary Schools in the Sukamakmur District - Bila, Nailah Salsa; Lengkana, Anggi Setia Lengkana; Rukmana, Anin (Universitas Majalengka, 2024)
This research is based on the fact that Physical Education learning in elementary schools in Sukamakmur District has not been running optimally due to inadequate infrastructure and very limited professional teaching staff in the field of physical education. This research aims to analyze how they carry out physical education learning and how they handle physical education learning. This research is qualitative. The method used is a questionnaire survey and interviews with data collection techniques using questionnaires and interviews. Where later, participants must fill out a questionnaire that the researcher provides, and interviews will be conducted with the selected participants. Participants in this research were class teachers in elementary schools in Sukamakmur District. The results of this research will be in the form of a description in which it can be seen how the class teacher handles physical education learning. If there are no teaching staff in the field of physical education, then what kind of learning is carried out by the class teacher? From the research that has been carried out, data is obtained that class teachers overcome them by 1) Making Plans, 2) Practicing, 3) Learning in Class, 4) Learning in the Field and the problems, namely 1) Environmental Conditions, 2) Not in the Field and 3) Lack of understanding. The hope is that it will become a reference for the government to distribute physical education teachers evenly so that physical learning can run optimally.